Effect of Bifidobacterium upon Clostridium difficile Growth and Toxicity When Co-cultured in Different Prebiotic Substrates - Valdés-Varela, L.; Hernández-Barranco, Ana M.; Ruas-Madiedo, Patricia; Gueimonde, Miguel (Frontiers in Microbiology, 2016)
The intestinal overgrowth of Clostridium difficile, often after disturbance of the gut microbiota by antibiotic treatment, leads to C. difficile infection (CDI) which manifestation ranges from mild diarrhea to life-threatening conditions. The increasing CDI incidence, not only in compromised subjects but also in traditionally considered low-risk populations, together with the frequent relapses of the disease, has attracted the interest for prevention/therapeutic options. Among these, probiotics, prebiotics, or synbiotics constitute a promising approach. In this study we determined the potential of selected Bifidobacterium strains for the inhibition of C. difficile growth and toxicity in different carbon sources. We conducted co-cultures of the toxigenic strain C. difficile LMG21717 with four Bifidobacterium strains (Bifidobacterium longum IPLA20022, Bifidobacterium breve IPLA20006, Bifidobacterium bifidum IPLA20015, and Bifidobacterium animalis subsp. lactis Bb12) in the presence of various prebiotic substrates (Inulin, Synergy, and Actilight) or glucose, and compared the results with those obtained for the corresponding mono-cultures. C. difficile and bifidobacteria levels were quantified by qPCR; the pH and the production of short chain fatty acids was also determined. Moreover, supernatants of the cultures were collected to evaluate their toxicity using a recently developed model. Results showed that co-culture with B. longum IPLA20022 and B. breve IPLA20006 in the presence of short-chain fructooligosaccharides, but not of Inulin, as carbon source significantly reduced the growth of the pathogen. With the sole exception of B. animalis Bb12, whose growth was enhanced, the presence of C. difficile did not show major effects upon the growth of the bifidobacteria. In accordance with the growth data, B. longum and B. breve were the strains showing higher reduction in the toxicity of the co-culture supernatants.